2016
DOI: 10.1097/rti.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Coronary-Pulmonary Artery Fistulas

Abstract: CPAFs are seen in a variety of clinical settings, from infants with advanced congenital heart disease to elderly patients who have undergone revascularization surgery. Although coronary artery fistulas have previously been described as rarely involving multiple coronary arteries, with the right coronary artery being most often involved, our series demonstrates that multiple fistulas are commonly present, with the most common pattern being between the left main/left anterior descending and the main pulmonary tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 64 publications
1
64
0
3
Order By: Relevance
“…The majority (89%) of CAFs drain into the pulmonary trunk rather than into other segmental pulmonary arteries. According to findings in a recent study by Verdini et al (41), two types of coronary-topulmonary artery fistulas occur. The first type is a single prominent fistulous connection between the LAD or RCA and the main pulmonary trunk…”
Section: Coronary Artery-to-pulmonary Artery Fistulamentioning
confidence: 92%
See 1 more Smart Citation
“…The majority (89%) of CAFs drain into the pulmonary trunk rather than into other segmental pulmonary arteries. According to findings in a recent study by Verdini et al (41), two types of coronary-topulmonary artery fistulas occur. The first type is a single prominent fistulous connection between the LAD or RCA and the main pulmonary trunk…”
Section: Coronary Artery-to-pulmonary Artery Fistulamentioning
confidence: 92%
“…When a CAF drains into the pulmonary arteries, the murmur is best heard in the second intercostal space, left of the sternum. At cardiac CT angiography, a coronary-to-pulmonary artery fistula appears as an abnormal contrast blush, which is also referred to as the contrast shunt sign, in a relatively less-opacified pulmonary trunk or as a well-visualized fistulous tract between the coronary artery and pulmonary trunk (41). Although previous study investigators (4,25) have reported CAFs originating from the RCA to be more common than those originating from the LCA, results of a recent systematic review (41) showed the LCA to be the most common origin site (84% of cases), followed by the RCA (38% of cases).…”
Section: Coronary Artery-to-pulmonary Artery Fistulamentioning
confidence: 99%
“…Management of CPFs could consist of conservative watching or surgical ligation or percutaneous interventional techniques including coil embolization and placement of covered stents across the origins of feeding arteries . Occasionally, CPFs can have complex architecture with multiple feeding arteries and their management could be more challenging .…”
Section: Discussionmentioning
confidence: 99%
“…Coronary-to-pulmonary artery fistulas are rare coronary connections (literature rates of <0.7%) most frequently originating from the left main coronary artery, the left anterior descending artery or the right coronary artery and draining into the main pulmonary artery [1]. Although they are often incidental findings (CTCA has increased diagnosis rates), patients may present with angina, dyspnoea, congestive heart failure, pulmonary hypertension, arrhythmias and sudden cardiac death.…”
Section: Answermentioning
confidence: 99%